EFFECTIVENESS OF HISTORICAL LEARNING MODELS INTEGRATED KALWEDO CULTURAL VALUE THROUGH PROBLEM BASED LEARNING TO IMPROVE STUDENTS' SOCIAL SOLIDARITY - RIFAI, RIFAI (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2019)
This study aims to analyze the effectiveness of the application of integrated historical learning models Kalwedo culture. Kalwedo culture is one of the local wisdom of the people of Southwest Maluku who have noble values ​​such as cooperation, mutual cooperation, mutual respect, and social care. The research method used is Research and Development, by collecting data through literature studies, interviews, surveys, pre-post test tests and questionnaires. Data is processed using SPSS to determine the level of effectiveness of the application of the learning model. The results of the study indicate that this learning model is effectively used. This can be seen in the statistical results of achievement abilities and attitude scores between the experimental class and the control class that have a significant difference. This is shown by the acquisition of the experimental posttest grade value of 99.96 and the control class posttest of 93.68. While the value for the T test was obtained at 2.785 with a significance level of 0.007. Significance level of 0.007 <0.025. Then Ho is rejected or there is a difference in average between the experimental class and the control class. So it can be concluded that there is a positive and significant increase in the class using the historical learning model integrated Kalwedo cultural values ​​through PBL. From the results obtained can be concluded that the model developed is effective if used in learning, especially learning history.